Islam, Humanity and the Indonesian Identity Reflections on History - Maarif, Ahmad Syafii (Debates on Islam and Society, 2018)
"Islam exists in global history with its richly variegated cultural and social realities. When these specific cultural contexts are marginalized, Islam is reduced to an ahistorical religion without the ability to contribute to humanity. This limited understanding of Islam has been a contributing factor in many of the violent conflicts in the present day. Reflecting on Islam in Indonesia, the world's third largest democracy, supporting the largest Muslim population, Ahmad Syafii Maarif argues for an understanding that is both faithful to Islam's essential teachings and open to constantly changing social and cultural contexts. Building on this, he then addresses critical contemporary issues such as democracy, human rights, religious freedom, the status of women, and the future of Islam. Through this book the breadth and depth of the ideas of one of Indonesia's foremost Muslim scholars are made accessible for English language readership."